2023
DOI: 10.1002/sstr.202200404
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Hydrogen Evolution Reaction Electrocatalysts for Commercial Alkaline Water Electrolysis

Abstract: With the further exploitation of renewable energy sources, electrochemical hydrogen evolution reaction (HER) is considered a key technology to solve environmental problems and achieve global carbon neutrality. Currently, alkaline water electrolyzers (AWEs) have been revitalized as a traditional electrolytic water production industry, yet they face great challenges in achieving new technological breakthroughs due to the catalytic properties of electrode materials. In alkaline media, besides the slow kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 182 publications
0
13
0
Order By: Relevance
“…We propose that the limitation in FE H2 we observe at much lower current densities can be related to the hydrogen bubble generation and detachment. The enlarging hydrogen bubbles which do not detach can induce the local inhibition of the mass transfer at the surfaces . Permeation of the electrolyte can also cause mass transfer issues beneath the CN x surface.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that the limitation in FE H2 we observe at much lower current densities can be related to the hydrogen bubble generation and detachment. The enlarging hydrogen bubbles which do not detach can induce the local inhibition of the mass transfer at the surfaces . Permeation of the electrolyte can also cause mass transfer issues beneath the CN x surface.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen is an important clean energy source that solves the energy crisis and achieves decarbonization. Alkaline water electrolysis (AWE) hydrogen production is one of the most mature and widely used hydrogen production technologies in the industry today. , Although AWE has encountered new opportunities in today’s society for green hydrogen production, it still needs high operating cell voltages along with high electricity energy input. The development of industrial-scale electrocatalysts suitable for industrial applications is of great significance to extend the service life of AWE and reduce preparation, operation, and postmaintenance costs . Currently, the commercially used electrocatalyst is a nickel–aluminum alloy (NiAl alloy, Raney Ni) sprayed on a porous Ni mesh.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the commercially used electrocatalyst is a nickel–aluminum alloy (NiAl alloy, Raney Ni) sprayed on a porous Ni mesh. This NiAl alloy can operate steadily for tens of thousands of hours at high current densities, even at high alkali concentration (6 M KOH), high operating temperature (60–80 °C), and high pressure (2–10 bar), but its poor catalytic activity and large overpotential result in high costs for hydrogen production. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Meanwhile, research has demonstrated that Ru-doped LDH also holds an outstanding absorption capability with hydrogen intermediates, 11,12 which is promising to catalyse the HER efficiently by decreasing the kinetic energy barrier of the Volmer step in the HER. 13 Nevertheless, there is still large room for electrolysis catalysts in industrial hydrogen production. More recently, efforts have been invested in catalysing the reaction under more practical conditions ( e.g.…”
mentioning
confidence: 99%